Pemahaman Kepala Sekolah dan Guru Tentang Program Penguatan Profil Pelajar Pancasila di SMP Negeri 1 Sukosewu Bojonegoro - Gista Tria Pamungkas; Warsono Warsono (Medan Resource Center, 2023)
This research aims to know the understanding of the Head of School and Teacher related to the profile of students Pancasila in SMP Negeri 1 Sukosewu Bojonegoro. This research focuses on the understanding of the Head of School and Teacher of the concept of Pancasila Student Profile. The approach in this research is qualitative with the type of evaluative research. Data collection methods, such as interviews and documentation. The results of research in general, the Head of School and Teacher understand and acknowledge the importance of the dimensions of believing, fearful, and noble morality; royong; independent; critical; and creative. However, there are differences in the dimensions of global independence, where their understanding still needs to be enhanced. The conclusion of this study is the need for improved understanding and implementation of the global independence dimension in the student profile of Pancasila in the 1st Sukosewu Bojonegoro State High School.